Simulación de un sistema de detección de chatter en la fresadora Paxton/Patterson a través de la medición de los parámetros eléctricos del motor de la máquina herramienta (2021)
This paper proposed a simulation of a chatter detection system, using the measurement of electrical parameters, which consists of a construction of a block model of a DC engine in the MATLAB-programSIMULINK for Paxton/Patterson milling machine tool, obtaining as a result the behavior of the system in order to validate this model by means of the analyses carried out to the fast transforms of Fourier and to the diagrams of lobes of stability to determine the points where the chatter exists in the process of milling